Features of the tactical training of gymnasts performing in group exercises - Kozhanova, O.; Gavrilova, N.; Tsykoza, E. (Slobozhanskyi herald of science and sport, 2019)
Purpose: to analyze the experience of trainers regarding the features of the use of tactical techniques in the construction of modern compositions of group exercises in rhythmic gymnastics.